Emotional Experience and Regulation in Juvenile Primary Headaches: A Cross-Sectional Pilot Study - Marina Miscioscia; Daniela Di Riso; Silvia Spaggiari; Mikael Poli; Giacomo Gaiga; Giacomo Randazzo; Maria Federica Pelizza; Laura Galdiolo; Alessia Raffagnato; Stefano Sartori; Irene Toldo (MDPI AG, 2022)
A headache is the most common neurological symptom in children. Its subtypes are migraine (MH) and tension-type headache (TTH). Internalizing rather than externalizing symptoms are more frequent in children with headaches, but little is known about the reasons why. We aim to: (a) examine the interplay between emotional experience, affective regulation, and internalizing symptoms in children suffering from primary headaches and their caregivers; (b) identify potential predictors of children with migraines' internalizing symptoms. Fifty children and adolescents with a diagnosis of primary headaches and their caregivers were compared to a sample of fifty-one healthy peers and caregivers. Self-reports and parent-reports were administered. Results indicate higher negative affect and internalizing symptoms and lower bodily awareness of emotions in the clinical sample (n = 50; Mage = 11.66, SD = 2.25) compared to controls (n = 51; Mage = 11.73, SD = 2.32); mothers of TTH children self-reported lower emotional awareness and higher difficulties in engaging in goal-directed behavior; a higher frequency of headaches was associated with greater emotional regulation difficulties. Internalizing symptoms were predicted by higher self-reported negative affect and parent-reported internalizing symptoms, and lower self-reported ability in the verbal sharing of emotions. These findings suggest the importance of assessing the psychological features linked to children with primary headaches' psychological well-being.